Effects of medical consortium policy on health services: an interrupted time-series analysis in Sanming, China - Xinmei Yang; Xinmei Yang; Xinmei Yang; Yang Chen; Chengyue Li; Chengyue Li; Chengyue Li; Mo Hao; Mo Hao; Mo Hao (Frontiers Media S.A., 2024)
ObjectivesChina has implemented reforms to enhance the operational efficiency of three-level medical services through medical consortiums (MCs). This study evaluated the impact of MCs reform on health services in Sanming, China.MethodsAn interrupted time-series analysis (ITSA) was conducted to assess the impact of MCs on changes in health service levels and trends across the overall situation of MCs and different institutional types within MCs, including county hospitals and grassroots medical institutions. The evaluation focused on various indicators such as outpatient and emergency visits, inpatients, average length of stay, occupancy rate of hospital beds, and hospital bed turnover times. Monthly data were collected from April 2015 to June 2019 through reports on the Sanming Municipal Health Commission website and the Sanming public hospital management monitoring platform.ResultsAfter the intervention of MCs reform, a significant increase was observed in the total number of inpatients (β3 = 174.28, p < 0.05). However, no statistically significant change was observed in the total number of outpatient and emergency visits (β3 = 155.82, p = 0.91). Additionally, the implementation of MCs reform led to an amplification in service volumes provided by county hospitals, with significant increases in the number of outpatient and emergency visits (β3 = 1376.54, p < 0.05) and an upward trend in the number of inpatients (β3 = 98.87, p < 0.01). However, no significant changes were observed under the MCs policy for grassroots medical institutions regarding the number of outpatient and emergency visits (β3 = −1220.72, p = 0.22) and number of inpatients (β3 = 75.42, p = 0.09).ConclusionThe Sanming MCs reform has achieved some progress in augmenting service volumes. Nevertheless, it has not led to an increase in service volumes at the grassroots medical institutions. There persists an insufficiency in the efficiency of services and a need for further improvement in primary healthcare. To address these concerns, it is imperative for county hospitals to offer targeted assistance that can enhance motivation among grassroots medical institutions. Besides the MCs should explore initiatives, including improved management of medical equipment, allocation of funding, and personnel resources.